Legume green manure partial replacement of fertilizers enhances soil microbial diversity and sustains wheat yield - Wang, Huiyan; Wang, Hui; Yang, He; Liu, Xiaoyu; Liu, Xinbao; Guan, Yongxiang; Shen, Yixin; Li, Jianlong; Yang, Dianlin; Sun, Zhengguo (Frontiers in Plant Science, 2025)
IntroductionThe excessive use of chemical fertilizers has severely impacted soil quality and the ecological environment of farmland, hindering the development of sustainable agriculture.MethodsThis study evaluated five treatments: conventional monoculture of winter wheat (Triticum aestivum L., CK), intercropping of winter wheat with Chinese milk vetch (Astragalus sinicus L., IM), crimson clover (Trifolium incarnatum L., IC), smooth vetch (Vicia villosa Roth., IS), and common vetch (Vicia sativa L., IV). Intercropping treatments all resulted in a 30% reduction in chemical fertilizer application compared to monocropping.ResultsThe results indicated that the IC treatment yielded wheat grain quantities most similar to CK. When the wheat reaches maturity, the IS treatment resulted in increases in soil pH and soil organic matter (SOM) of 6.73% and 25.76%, respectively (P < 0.05). The greatest enhancements of soil urease (URE) and acid phosphatase (ACP) activities were observed with the IM treatment, which showed increases of 32.24% and 57.58%, respectively, compared to wheat monoculture. The IC treatment also enhanced soil sucrose (SUC) activity by 15.24% (P < 0.05). Intercropping with leguminous green manure improved the diversity and richness of soil bacterial communities, as evidenced by increases in the Chao 1 and Shannon indices, along with higher relative abundances of Proteobacteria and Sphingomonas. DiscussionSelecting the appropriate leguminous green manure is crucial. Non-climbing varieties are generally preferred. We believe that intercropping crimson clover in wheat fields can not only maintain the yield of the main crop, reduce agricultural production costs, but also improve the micro-ecological environment of the farmland, providing a novel solution for breaking through traditional wheat farming models.